Catholic responses to peacebuilding, climate change, and extractive industries - Holden, William N.; Nadeau, Kathleen (2020)
The paper overviews the Catholic response to addressing climate change-related problems and its peacekeeping efforts in the conflict zones impacted by natural and manmade disasters. It argues for the importance of transforming the dominant economic paradigm based on extracting natural resources for sale around the world, into a more environmentally sound approach that promotes the sustainable use of renewable energy sources and the greenifying of the natural environment. It calls for a world in which human are seen as stewards of creation and their cities constructed with the view of tendering and caring for other living sentient species and life forms to better ensure ecological balance and a better-quality for future generations to come.
Keywords: Laudato Si; Climate change; Greenhouse gases; Sustainability; Social justice